2020
DOI: 10.1111/tbed.13440
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of the re‐emerged avian leukosis virus in China, 2018–2019

Abstract: Since early 2018, avian leukosis virus (ALV) has re‐emerged throughout six provinces in Northeast and East of China and caused huge economic losses. In different farms, there are significant differences in clinical symptoms, including morbidity, mortality and location of tumours, on affected animals, which implies that the present strains may have different origins and molecular characteristics. In this study, a systematic epidemiological investigation was conducted in 21 farms in six provinces. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Since the rst strain of ALV-J, HPRS-103, was isolated from meat-type breeder chickens in the UK in 1988, it has rapidly spread around the world, causing severe economic losses to the poultry industry [4,14].…”
Section: Discussionmentioning
confidence: 99%
“…Since the rst strain of ALV-J, HPRS-103, was isolated from meat-type breeder chickens in the UK in 1988, it has rapidly spread around the world, causing severe economic losses to the poultry industry [4,14].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, local Chinese chickens are subjected to consistent ALV-J infection ( 5 ). Recently, analysis of the re-emerging outbreak of ALV-J in China indicated that there are new strains with the same ancestors, but they had gone through different evolutionary trajectories ( 6 ). Those new isolated ALV-J strains show salient differences in clinical symptoms compared with those from the early 2000s, including morbidity, mortality, and organ type of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Although ALV has been eradicated in avian flocks in most developed countries, ALV infection and prevalence is still present in China. Almost all chicken breeds, including white-feather broilers, layers, yellow-feather broilers and especially Chinese indigenous chickens, have been affected by ALV epidemics [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%